CODE MIXING IN THE CLASSROOM INTERACTION OF SMKN 7 MEDAN - Muhammad Azmi; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
The objective of this study is to find out the type of code-mixing used by theteacher and students and the factors causing the teacher and students mix thelanguage in classroom interaction. Code-mixing is a bilingualism phenomenonwhich has become very popular in society. It is used to prevent misunderstandingsuch the teacher and students in classroom interaction. This study was conductedby using descriptive qualitative design. The subjects of this study were the teacherand students from tenth grade of hotel accommodation in SMKN 7 Medan. Thedata were collected by recording the teacher and students’ utterances in classroominteraction, the interview result of teacher and questionnaire of students. From theresearch, it was found the type of code-mixing used by the teacher and studentswere word insertion, phrase insertion, and clause insertion. All of data belongs toouter code-mixing and the factors causing teacher did the code-mixing werespeaker partner, bilingual or multilingual, and absence of vocabulary. And for thestudents, according to the percentages of their questionnaire result the data showsthat out of 24 students 45,8% of them chose speaker partner as their reason did thecode mixing, 8,3% chose bilingual or multilingual, and 45,9% chose absence ofvocabulary.